PEDAGOGICAL ASPECTS OF USING MODERN SPORTS EQUIPMENT FOR 17-20 YEAR OLD STUDENTS - Liudmyla V. Shuba; Victor A. Shuba; Victoria V. Shuba (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2022)
The theory and practice of professional training at higher educational institutions as a pedagogical problem is closely linked to social and economic development in society, which is now the focus of many professionals from around the world. This is due to the fact that students are the future of the country. Physical education provides a unique and varied medium for learning. It develops students physically, intellectually, emotionally, socially, aesthetically, and creatively. It promotes the overall development of each student as a whole person. Physical education fosters diversity of skills and learning; it fosters practical use of these skills in different situations, and it fosters individual as well as group creativity in the use of these skills. Physical education encourages individual as well as team development. It encompasses a broad range of human feelings, emotion, and experiences. Students become increasingly more independent as their daily lives become more complex and diversified. Students begin to make decisions and choices in taking increased responsibility for themselves. Quality physical education programs provide students conceptual and practical understanding of: 1) health-related physical fitness, and 2) how to maintain a health-related level of physical fitness. Physical education plays a vital part in helping students maintain and refine the skills and knowledge needed to select physical activities to use throughout their lives. The paper demonstrates a new way for modernization of physical education system for 17–20 year-old girls with the use of groove machines in the gym. Groove machines typically emphasize the development of specific muscle groups. Muscle groups can be isolated, muscle imbalances can be corrected, and weak areas can be strengthened. Groove machines are sometimes more suited to strengthen muscles that are more difficult to target with free weights, such as the lats and hip ab/adductors. Limitations lie in the coordination of muscle groups for sports. In the process of method development we have kept all educational themes, hours and lesson structure, but have divided semesters into complexes. For more effective mastering of the learning material we have added new themes to the theoretical base. The chosen training methods must be coordinated with all other training to produce optimal competitive performance. The method of strength skills development has been elaborated. In addition, position requirements and individual differences further define the goals of the strength training program. The positive influence of this methodology on students’ level of physical training has been demonstrated.